2015
DOI: 10.1614/wt-d-15-00012.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of LibertyLink and WideStrike Cotton to Varying Rates of Glufosinate

Abstract: Field studies were conducted in Alabama, Arkansas, Georgia, Louisiana, Mississippi, North Carolina, and Tennessee during 2010 and 2011 to determine the effect of glufosinate application rate on LibertyLink and WideStrike cotton. Glufosinate was applied in a single application (three-leaf cotton) or sequential application (three-leaf followed by eight-leaf cotton) at 0.6, 1.2, 1.8, and 2.4 kg ai ha−1. Glufosinate application rate did not affect visual injury or growth parameters measured in LibertyLink cotton. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
5
9
0
Order By: Relevance
“…typical use rate when applied once or twice at growth stages ranging from 2-to 12-leaf. Resistance was similar to that described in previous research with LibertyLink and GlyTol + LibertyLink cotton (Dodds et al 2015;Irby et al 2013;Sweeney and Jones 2014;Wallace et al 2011). In other work (Richburg et al 2015; Dow AgroSciences internal research reports, unpublished data), Enlist cotton has been shown to be very tolerant to 2,4-D applied topically.…”
Section: Resultssupporting
confidence: 88%
“…typical use rate when applied once or twice at growth stages ranging from 2-to 12-leaf. Resistance was similar to that described in previous research with LibertyLink and GlyTol + LibertyLink cotton (Dodds et al 2015;Irby et al 2013;Sweeney and Jones 2014;Wallace et al 2011). In other work (Richburg et al 2015; Dow AgroSciences internal research reports, unpublished data), Enlist cotton has been shown to be very tolerant to 2,4-D applied topically.…”
Section: Resultssupporting
confidence: 88%
“…The results of this study support previous research that WideStrike cotton is more sensitive to postemergence applications of glufosinate, compared to other cotton cultivars such as LibertyLink (Marten and Jordan 1979). Additionally, this study supports previous research that tank mixtures of S-metolachlor with glufosinate can result in greater injury than glufosinate applied alone (Dodds et al 2015). According to this research, nozzle type does not have a significant effect on visible crop injury when comparing identical treatments within cultivars in most comparisons.…”
Section: Seed Cotton Yieldsupporting
confidence: 87%
“…A 110015 Turbo TeeJet Induction (TTI)® nozzle (TeeJet Technologies, Glendale Heights, IL) induction nozzle producing ultra-coarse droplets, or an 110015 extended-range (XR) flatfan nozzle (TeeJet Technologies, Glendale Heights, IL) producing fine droplets were used to apply to four-leaf and eight-leaf cotton. The trial was maintained weed free through methods similar to Dodds et al (2015) by the use of preemergence herbicides and hand weeding. The center two rows of each four-row plot were harvested using a spindle picker modified for small-plot harvesting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations